Development of a new loop-mediated isothermal amplification test for the sensitive, rapid, and economic detection of different genotypes of Classical swine fever virus - Bohórquez, Jose Alejandro; Muñoz-Aguilera, Adriana; Lanka, Saraswathi; Coronado, Liani; Rosell, Rosa; Alberch, Mònica; Maddox, Carol W.; Ganges, Llilianne (Frontiers in Cellular and Infection Microbiology, 2024)
Background Classical swine fever virus (CSFV) remains one of the most important pathogens in animal health. Pathogen detection relies on viral RNA extraction followed by RT-qPCR. Novel technologies are required to improve diagnosis at the point of care. Methods A loop-mediated isothermal amplification (LAMP) PCR technique was developed, with primers designed considering all reported CSFV genotypes. The reaction was tested using both fluorometric and colorimetric detection, in comparison to the gold standard technique. Viral strains from three circulating CSFV genotypes were tested, as well as samples from infected animals. Other pathogens were also tested, to determine the LAMP specificity. Besides laboratory RNA extraction methods, a heating method for RNA release, readily available for adaptation to field conditions was evaluated. Results Three primer sets were generated, with one of them showing better performance. This primer set proved capable of maintaining optimal performance at a wide range of amplification temperatures (60°C - 68°C). It was also able to detect CSFV RNA from the three genotypes tested. The assay was highly efficient in detection of samples from animals infected with field strains from two different genotypes, with multiple matrices being detected using both colorimetric and fluorometric methods. The LAMP assay was negative for all the unrelated pathogens tested, including Pestiviruses. The only doubtful result in both fluorometric and colorimetric LAMP was against the novel Pestivirus italiaense, ovine Italy Pestivirus (OVPV), which has proven to have cross-reaction with multiple CSFV diagnostic techniques. However, it is only possible to detect the OVPV in a doubtful result if the viral load is higher than 10000 viral particles. Conclusion The results from the present study show that LAMP could be an important addition to the currently used molecular diagnostic techniques for CSFV. This technique could be used in remote locations, given that it can be adapted for successful use with minimal equipment and minimally invasive samples. The joined use of novel and traditional diagnostic techniques could prove to be a useful alternative to support the CSF control.